Implementasi Putusan Serta Merta (Uitvoerbaar Bij Voorraad )Dalam Undang-Undang Nomor 2 Tahun 2004 Tentang Penyelesaian Perselisihan Hubungan Industrial - Amin, Muhammad Nur (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2021)
The position of the verdict immediately explicitly provided for Article 108 of Law No. 2 of 2004 on The Settlement of Indutsrial Disputes as a solution to restore the rights of workers/laborers in a rapid, accurate, and fair. However, in practice in the judiciary, especially in The Industrial Relation Court very rarely judge the verdict immediately (Uitvoerbaar Bij Voorraad) ruled that the reasons for decision will be in accordance with the Supreme Court Circular No. 3 of 2000. So, referenced in decisions is SEMA while law regulate the verdict. Therefore, it takes courage of a judge in the verdict immediately (Uitvoerbaar Bij Voorraad) based on the legislation that has been set so that the decision produced can provide justice for litigants.